Mendidik dan Mendiagnosa Anak Usia Dini yang Mempunyai Gangguan Autis dengan Mengetahui Problem-Problemnya - Hayyan Ahmad Ulul Albab (JCE (Journal of Childhood Education), 2018)
Autism is a lifelong disability that affects a person in social communication, social interaction, dealing with his environment and the imagination of a child who bears autism is like aliving in his own world. Lack of a child's ability to engage in understanding that includes, understands language, plays, and communicates with others. A diagnosis that a child has autism is by referring to ICD-10 (International Clasification of Disease) or using formulation in DSM-IV (Diagnostic Statistical Manual). The types of therapy that can be given to children with autism are behavioral therapy, occupational therapy, speech therapy, socialization with the aim to eliminate unnatural behavior, biomedical therapy (drugs, vitamins, minerals, food supplements), socialization to regular schools and School of Children with Special Needs. The problem of autistic students that will be faced during school age is Communication Abilities, Social Skills, Behavior Problems, Adaptive Living Skills problem in understanding the world and dificult behavior and emotional problems